2016
DOI: 10.1038/srep20520
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic infection of two viruses MCMV and SCMV increases the accumulations of both MCMV and MCMV-derived siRNAs in maize

Abstract: The co-infection of Maize chlorotic mottle virus (MCMV) and Sugarcane mosaic virus (SCMV) can cause maize lethal necrosis. However, the mechanism underlying the synergistic interaction between these two viruses remains elusive. In this study, we found that the co-infection of MCMV and SCMV increased the accumulation of MCMV. Moreover, the profiles of virus-derived siRNAs (vsiRNAs) from MCMV and SCMV in single- and co-infected maize plants were obtained by high-throughput sequencing. Our data showed that synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 58 publications
4
93
0
5
Order By: Relevance
“…Northern blotting was performed with [a-32 P]dCTP randomly labeled cDNA probes, which were from 62 to 673 nucleotides of the GFP sequences. The probes were labeled, and the blots were probed and washed as reported previously (Xia et al, 2016). Approximately 30-mg total RNA samples were prepared to detect GFP siRNAs, and the blots were probed and washed as described previously (Xia et al, 2014).…”
Section: Gfp Imaging and Rna Gel-blot Analysismentioning
confidence: 99%
“…Northern blotting was performed with [a-32 P]dCTP randomly labeled cDNA probes, which were from 62 to 673 nucleotides of the GFP sequences. The probes were labeled, and the blots were probed and washed as reported previously (Xia et al, 2016). Approximately 30-mg total RNA samples were prepared to detect GFP siRNAs, and the blots were probed and washed as described previously (Xia et al, 2014).…”
Section: Gfp Imaging and Rna Gel-blot Analysismentioning
confidence: 99%
“…A number of devastating crop diseases are the outcomes of viral synergism222324. Viral synergism can alter viral traits such as virus accumulation202325, tissue tropism26, host range27 and transmission rate28. There is accumulating evidence that interviral synergy can affect the characteristics of vsiRNAs derived from co-infecting viruses2529.…”
mentioning
confidence: 99%
“…Viral synergism can alter viral traits such as virus accumulation202325, tissue tropism26, host range27 and transmission rate28. There is accumulating evidence that interviral synergy can affect the characteristics of vsiRNAs derived from co-infecting viruses2529. It has been reported that synergistic interaction between crinivirus Sweet potato chlorotic stunt virus (SPCSV) and begomovirus Sweet potato leaf curl virus isolate StV1 in sweet potato leads to specific changes in the relative abundance and distribution of SPCSV-derived siRNAs, implying a distinctive influence of begomoviruses on RNA silencing of SPCSV in synergy29.…”
mentioning
confidence: 99%
“…The crude extracts were centrifuged at 12,000×  g for 15 min at room temperature, and the resulting supernatant (15 Όl per sample plus 15 Όl 2× SDS loading buffer) was electrophoresed in 12.5% SDS-PAGE gels followed by transferring proteins to nitrocellulose membranes performed as previously reported41. The membranes were then probed with the MCMV-specific monoclonal antibody31 followed by a goat anti-mouse secondary antibody conjugated to horseradish peroxidase (Bio-Rad, Los Angeles, CA, USA).…”
Section: Methodsmentioning
confidence: 99%